Aisyiyah dan Kiprahnya dalam Pembinaan Keluarga Sakinah - Adawiah, Rabiatul (IAIN Antasari Banjarmasin, 2013)
Forming an ideal family is not as easy as turning the palm of the hand , yet it requires immence effort, sacrifice and also strong awareness. Women have an important position in the familyand play significant roles to help create an ideal family. This study tries to describethe pursuit of womens organizationsâAisyiyah, in its part in constructing an ideal family in South Kalimantan. The formulation of problem in this study is how the concept of an ideal family presented by Aisyiyah in South Kalimantan, and how the pursuit of womens organizations in fostering ideal family. The result of the study shows that Aisyiyahâs concept about family is known as the